Clinical Image Coregistration Variability on a Dedicated Radiosurgery Unit. Issue 1 (July 2019) - Ruschin, Mark; Sahgal, Arjun; Soliman, Hany; Myrehaug, Sten; Tseng, Chia‐Lin; Bola, Ruby; Yeboah, Collins; Sarfehnia, Arman; Chugh, Brige; Eriksson, Markus; Nordström, Håkan; Lee, Young
Abstract : BACKGROUND: : On a new dedicated radiosurgery unit enabling frameless treatments, a cone‐beam computed tomography (CBCT) can be used for stereotactic definition. Since magnetic resonance imaging (MRI) is used to delineate target, reproducible MRI‐to‐CBCT coregistration is vital for accurate target localization. OBJECTIVE: : To evaluate reproducibility of image coregistration in patient images. METHODS: : Three types of coregistration (source‐to‐target) were analyzed: (1) MRI‐to‐CT; (2) MRI‐to‐CBCT; and (3) CT‐to‐CBCT. For each patient (n = 15), each coregistration type was independently performed 5 to 30 times (total: 465 coregistrations). Each coregistration yielded a transformation matrix, which was subsequently applied to transform every point in the source image to stereotactic coordinates. Two metrics were measured: (1) target registration error (TRE): mean distance between the registered position of each target point and the average registration position of that point; (2) compound registration error (CRE): mean spatial difference between stereotactic coordinates using (A) MRI‐to‐CT‐to‐CBCT and (B) MRI‐to‐CBCT. RESULTS: : The median (range) of TRE was 0.11 mm (0.06–0.22 mm), 0.17 mm (0.10–0.36 mm), and 0.12 mm (0.08–0.21 mm) for MRI‐to‐CT, MRI‐to‐CBCT, and CT‐to‐CBCT, respectively. The TRE for MRI‐to‐CBCT was statistically higher than the other 2 methods ( P < .01). The median (range) of CRE was 0.44 mm (0.22–0.59 mm). The maximum point CRE between patients ranged from 0.37–1.15 mm when considering all MRI points, but reduced to 0.31–0.90 mm within the central 16 cm. The CRE varied across the image volume, and typically was minimized near the center. CONCLUSION: : The variation in image coregistration is within 0.2 mm, indicating a high degree of reproducibility. The CRE varies throughout the head but is submillimeter in the central 16 cm region.